2023
DOI: 10.3847/1538-4357/acdeef
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Stellar Cluster and Feedback-driven Star Formation in the Galactic Mid-infrared Bubble [HKS2019] E70

Abstract: We present a comprehensive analysis of the Galactic mid-infrared bubble [HKS2019] E70 (E70) by adopting a multiwavelength approach to understand the physical environment and star formation scenario around it. We identified a small (radius ∼1.7 pc) stellar cluster inside the E70 bubble, and its distance is estimated as 3.26 ± 0.45 kpc. This cluster is embedded in the molecular cloud and hosts massive stars, as well as young stellar objects (YSOs), suggesting active star formation in the region. The spectral typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…As this region shows many signatures of star-forming activities, we can expect young populations of stars to be embedded in this region. As these young populations (or YSOs) are usually associated with the circumstellar disk, we identified/classified them based on their excess IR emission (for details, please refer to Verma et al 2023). We found both Class I and Class II YSOs in our selected FOV of this region and their locations are shown in panel (c) of Figure 5.…”
Section: Physical Environment Around Ngc 2316 Clustermentioning
confidence: 95%
See 2 more Smart Citations
“…As this region shows many signatures of star-forming activities, we can expect young populations of stars to be embedded in this region. As these young populations (or YSOs) are usually associated with the circumstellar disk, we identified/classified them based on their excess IR emission (for details, please refer to Verma et al 2023). We found both Class I and Class II YSOs in our selected FOV of this region and their locations are shown in panel (c) of Figure 5.…”
Section: Physical Environment Around Ngc 2316 Clustermentioning
confidence: 95%
“…To understand the structure of the NGC 2316 cluster, we generated the stellar surface density map of the region by the nearest neighbor method (Gutermuth et al 2005). This was done in a grid having a size of 10″ and for the twentieth nearest star, using the NIR catalog (for details, please refer to Verma et al 2023). We overlaid the estimated isodensity contours (red curves) in Figure 1.…”
Section: Physical Properties Of Ngc 2316 Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…E70-MIR bubble E70, first cataloged by Hanaoka et al (2019). Verma et al (2023b) reported that it is located at a distance of 3.26 kpc, has a small stellar clustering of radius ∼1.7 pc, and is hosting a massive O9V star possessing positive feedback and "collect and collapse scenario" might be a probable star formation scenario at the rim of this bubble. KPS0620-KPS0620 is a poorly studied star cluster that is located at a distance of 6.1 kpc according to Buckner & Froebrich (2013), whereas Kharchenko et al (2013) reported it to be located at 2.2 kpc.…”
Section: Source Selectionmentioning
confidence: 99%
“…The system temperature includes noises from the antenna (the optical system, the membrane, and the dome), the receiver, and the atmosphere (Su et al 2019). A subset of this data comprising the E70 bubble has already been presented in Verma et al (2023b). The lowest level value for both the contours is the mean value with a step size of 1σ.…”
Section: Molecular Line Datamentioning
confidence: 99%